Policy Evaluation to Changes Savings Value Guaranteed by Deposit Insurance: Indonesia Study - Patriginari, Ginung; Nugroho, Bernardus Yuliarto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
LPS is permitted to propose changes to the deposit insurance coverage limitations. The evaluation dimensions of effectiveness and efficiency are used as the primary assessment criteria in this paper to analyze these adjustment criteria utilizing the evaluation dimensions theory. Data on savings account distribution are all used. According to the analysis's findings, just 0.1 percent of all banking accounts hold 60.42 percent of the sector's total nominal deposits. The study comes to the conclusion that the standards used to gauge the level of deposit protection offered by LPS do not entirely correspond to the theoretically derived dimensions of efficiency and effectiveness. This study emphasizes the possibility of systemic risk by focusing on the dynamics of banking customers' deposits, account distribution, and nominal distribution of bank deposits.